2007
DOI: 10.2174/156720507783018226
|View full text |Cite
|
Sign up to set email alerts
|

Novel Multifunctional Anti-Alzheimer Drugs with Various CNS Neurotransmitter Targets and Neuroprotective Moieties

Abstract: Traditionally, drug design programs are focused on optimizing the specificity of lead compounds against a carefully selected drug target. Disappointingly, this approach to discover a "magic bullet" drug has not met with the expected success for CNS disorders. Transcriptomics and proteomic profiling of neurodegenerative diseases have indicated that they are poly-etiological in origin and that the processes leading to neuronal death are multifactorial. An emerging concept is the design of drug ligands that modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 87 publications
(144 reference statements)
0
16
0
Order By: Relevance
“…Much research remains to be done to fully characterize the potential targets and therapeutic approaches to optimize mGluRs as a multipotential intervention. Recent reviews extensively outline critical considerations for the development of mutli-target-directed ligands for treatment of neurodegenerative disorders 10, 93…”
Section: Resultsmentioning
confidence: 99%
“…Much research remains to be done to fully characterize the potential targets and therapeutic approaches to optimize mGluRs as a multipotential intervention. Recent reviews extensively outline critical considerations for the development of mutli-target-directed ligands for treatment of neurodegenerative disorders 10, 93…”
Section: Resultsmentioning
confidence: 99%
“…The development of clinically viable drugs that act as disease-modifying agents rather than providing only symptomatic relief is therefore crucial for the treatment of this devastating disorder. PD is a complex disease with multiple pathogenic factors and thus it would be of great value to develop novel therapeutics that can act on various mechanisms associated with the overall disease process (Van der Schyf et al 2007, Youdim 2010, Youdim 2013). In our continued efforts to discover multi-pronged therapeutics targeting multiple complex factors involved in PD neuropathology, we have developed a series of dopamine D2/D3 agonist compounds that possess potential antioxidant, iron-chelator, and neuroprotective properties (Li et al 2010, Gogoi et al 2011, Johnson et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…16 The concept of synergistic actions of multiple-functions from a singlemolecule drug has been realized in the use of Sutent with inhibition of various kinases for successfully curing several kinds of cancers. 18 Therefore, the new potential approaches pioneered by Youdim 16,19 have been developed expressly to target multiple sites in the brain with single molecular entities for the treatment of memory and cognition impairment; and single drugs developed with a network approach target two or more of the following factors synergistically for cognitive enhancements: AChE, ␤-amyloid (A␤), tau protein, monoamine oxidase, metal ions, reactive oxygen species (ROS), and neuroprotection. Encouragingly, well-controlled trials of memantine/donepezil dual therapy have shown superior efficacy in moderate to severe AD patient subgroups.…”
Section: Introductionmentioning
confidence: 99%